A coupled hydro-mechanical constitutive model for unsaturated frictional and cohesive soil. (June 2018) - Gholizadeh, Esmaeel; Latifi, Manoucher
Abstract: The present study has developed a constitutive model for both saturated and unsaturated soils. The model considers the effect of mechanical and hydraulic loading on the soil behavior in critical state framework. The mechanical part has separate mechanisms, deviatoric mechanism taking advantage of multi-yield surface plasticity, and isotropic mechanism with classical plasticity formulation. The water retention part is based on the bounding surface concept. Comparison of experimental data and model predictions for saturated and unsaturated states in frictional and cohesive soils, validates the model performance considering soil behavior under different drainage and loading conditions by using one set parameters.